PENINGKATAN KECERDASAN LOGIKA MATEMATIKA DI TAMAN KANAK-KANAK GEMBALA BAIK PONTIANAK - Sutini, Maria Geroti (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract: The purpose of this study to increase intelligence through the use of mathematical logic game find match picture in children aged 5-6 years with descriptive methods. In general it can be concluded that: 1) Planning of learning by using the find match game to improve intelligence picture mathematical logic in children aged 5-6 years are categorized as "good". 2) Implementation of learning by using the find match game to improve intelligence picture mathematical logic in children aged 5-6 years are categorized as "good". 3) Increased mathematical logic intelligence in children aged 5-6 years include: child pair an image with ABCD-ABCD pattern which can fly up 85%, according to the image pair of children increased by 80% partner, child looking pair of images is lost increases 80%.   Keywords: Mathematical Logic, Game Find Match Picture